Kesenjangan Gender dalam akses pendidikan bagi perempuan - Maknun, Hurin In (Maliki Interdisciplinary Journal, 2024)
This article discusses the gender gap felt by women that results in differences in rights between men and women. The gap in question is not to violate or surpass the nature of men who are indeed in some aspects by Allah swt has been given advantages over women, but rather the implementation of human rights that should not look at gender in this case. The human rights referred to in this article are the rights in equal education regardless of gender. Women have the right to be equal in pursuing and obtaining higher education. This article also mentions the supporting factors why women's access to education is different from men from the views of several layers of society.